Bigger and Different: Beginning to Understand the Role of High-Speed Rail in Developing China's Future Supercities. Issue 1 (2016) - Wu, Qiyan; Perl, Anthony; Sun, Jingwei
The development of high-speed rail (HSR) is transforming the landscape of China by enabling new forms of urban and regional expansion. Some of these spatial and economic effects mirror past experience with HSR infrastructure in Japan and Western Europe. But the scale of China's HSR infrastructure and its role in providing that country's intercity mobility are sufficiently greater than previous HSR development that new spatial effects can be expected. This paper takes the first step in explaining this transformation by creating an analytical framework to differentiate three modes of spatial development that can be associated with distinct configurations of HSR operation in China. An initial assessment of these transportation development genres is offered, and an agenda for future research into the catalytic role of HSR in China's development of supercities with more than 130 million people is presented.